AIP mutation in pituitary adenomas in the 18th century and today. - Chahal, H; Stals, K; Unterländer, M; Balding, D; Thomas, MG; Kumar, A; Besser, G; Atkinson, AB; Morrison, P; Howlett, T; Levy, M; Orme, S; et al. (2011)
Gigantism results when a growth hormone-secreting pituitary adenoma is present before epiphyseal fusion. In 1909, when Harvey Cushing examined the skeleton of an Irish patient who lived from 1761 to 1783, he noted an enlarged pituitary fossa. We extracted DNA from the patient's teeth and identified a germline mutation in the aryl hydrocarbon-interacting protein gene (AIP). Four contemporary Northern Irish families who presented with gigantism, acromegaly, or prolactinoma have the same mutation and haplotype associated with the mutated gene. Using coalescent theory, we infer that these persons share a common ancestor who lived about 57 to 66 generations earlier.